Temperature dependence of collisional induced absorption (CIA) bands of CO2 with implications for Venus' atmosphere. (January 2018) - Stefani, Stefania; Snels, Marcel; Piccioni, Giuseppe; Grassi, Davide; Adriani, Alberto
Highlights: Collision induced bands of carbondioxide were recorded for different densities and temperatures. The temperature dependence of collision induced bands has been studied. Integrated band intensities have been provided for Venus' atmosphere. The role of dimers in collision induced bands is discussed. Abstract: The intensity and temperature dependence of four CO2 collision induced absorption (CIA) bands in two spectral regions, 1100–1600 cm − 1 and 2500–3200 cm − 1 have been investigated. The measurements have been performed with a Fourier Transform InfraRed (FT-IR) spectrometer operating in a wide spectral range, from 350 to 25000 cm − 1 (0.4 to 28.5 µm) with a spectral resolution of 2 cm − 1, interfaced with a high pressure-high temperature (HP-HT) absorption cell with an optical path of about 2 cm. While the integrated band intensity of allowed bands shows a linear dependence versus density, the collision-induced integrated band intensity increases quadratically with the density, due to the absorption by pairs of molecules, which allows identifying the CIA bands unambiguously. While below 300 K the binary integrated absorption coefficients exhibit a pronounced temperature dependence due to the presence of dimers, a much weaker temperature dependence has been found above 300 K. The results are important for the radiative transfer calculations of Venus' atmosphere. The integrated band intensities of the studied bands have been calculated for Venus' atmosphere from 40 km down to the surface by extrapolating the binary integrated absorption coefficients to the relevant temperatures.